The Importance Of The Study Of Radiosensitivity In Human Genetic Disorders - RADHA SARASWATHY,; MEENA J,; K.M.MARIMUTHU, (International Journal of Pharma and Bio Sciences, 2012)
It is a well established radiobiological concept that no radiation doses can be considered completely safe. Radiobiologists have been struggling to estimate the health risks from low doses of radiation in human beings for decades. Little is known on the underlying predisposition of the individuals so affected. Hence in this study few established precancerous chromosomal syndromes were subjected to radiation 1) to check for the existence of increased radiosensitivity as measured by chromosomal endpoint, 2) if any syndromes with high radiosensitivity are non tumorigenic and 3) whether radiosensitivity is a prerequisite for the induction of cancer. Our results showed that the radiosensitivity of the chromosomes is significantly greater both in patients and their relatives of high myopia than the normal. Further, the type of chromosomes that are more frequently involved in the production of break points than those of other chromosomes vary in different human genetic disorders studied.